TRIAL OF DEMOCRACY VERSUS DEMOCRATIC TRIUMPHALISM: A FOCUS ON GHANA - Collins Adu-Bempah Brobbey (European Scientific Journal, ESJ, 2014)
The volume of empirical literature on Ghana’s democratization is overwhelming. Two contrasting positions have come to dominate the Ghanaian democratization political discourses. While some Afro-optimist scholars argue that Ghana is the model of democracy in Africa and hence it is in the era of democratic triumphalism, on the contrary, other Afropessimist scholars contend that Ghana has since independence been experiencing a complex and contradictory historical legacy of democratic governance - where liberalism exists side by side with patronage politics and hence it is still in the era of trial of democracy. Thegoal of this paper is to investigate how Ghana’s democratic governance exists side by side with widespread cronyism and nepotism. The data for this paper came from scholarly articles, newspaper reports, and in-depth interviews.. This paper draws a number of conclusions. First, on the theoretical level, Ghana has a beacon of democratic rule and hence it is a model of Africa’s democracy. Second, empirically, the country’s relative electoral democratic success story is largely cosmetic due to pervasive cronyism and nepotism which impede active civic political participation. It thus, recommends institutional reforms not only to promote domestication and socialization of democratic norms, culture and values but also making it internalizeable and enforceable.